Crohn's disease in Bangladeshis and Europeans in Britain: an epidemiological comparison in Tower Hamlets. - Probert, C. S. (BMJ Group, 1992)
The incidence of Crohn's disease in a defined Bangladeshi community was assessed in a retrospective, epidemiological study in the London Borough of Tower Hamlets from 1972 to 1989. The borough population of 164,000 includes over 28,000 Bangladeshis. Potential cases were identified from hospital pathology and medical records. There were 99 cases of Crohn's disease during the study period, of which five were Bangladeshi. The mean standardized incidence in Bangladeshis was 1.2/10(5)/year in the 1970s and 2.3/10(5)/year in the 1980s compared with 3.8/10(5)/year and 4.1/10(5)/year in Europeans, and 4.6/10(5)/year and 5.4/10(5)/year in West Indians, respectively. None of the changes with time was statistically significant. There were no cases amongst Hindus. The relative risk to Europeans, compared to Bangladeshis, was 2.5 during the 1970s and 2.0 in the 1980s. The difference between European incidence and that of other ethnic groups was not statistically significant; however, the number of Bangladeshi cases was small (five), and diminishes the power of the study. The apparent similarity of the incidences of Crohn's disease in Bangladeshis and Europeans contrasts with findings in other South Asians. Further investigations of the differences in incidence of Crohn's disease in South Asians is needed.